Transpapillary Pancreatoscopy in an Emergency Hospital - L. L. Generdukayev; Yu. S. Teterin; D. A. Blagovestnov; E. S. Yeletskaya; K. A. Nugumanova; P. A. Yartsev (Неотложная медицинская помощь)
Endoscopic pancreatoscopy is a highly informative method for visualizing the pancreatic ducts, which allows them to be accurately diagnosed and treated in a minimally invasive way. The SpyGlass direct imaging system is currently the most widely used device. Specially designed endoscopes and smaller diameter instruments allow direct visualization of the bile and pancreatic ducts to be performed. In this article, the first clinical case of successful direct visualization with SpyGlass is reported, which was conducted in the SBHI N.V. Sklifosovsky Research Institute for Emergency Medicine in a patient with chronic calcifying pancreatitis complicated by wirsungolithiasis.